A comparative study of several boundary conditions on the body surface for the meshless electromagnetic scattering method. (November 2020) - Gao, Yukun; Chen, Hongquan; Xu, Shengguan; Zhang, Jiale; Cao, Cheng; Gao, Huanqin
Abstract: In order to accurately calculate the radar cross sections (RCS) of stealth aircrafts by using the meshless method, several typical body surface boundary conditions from finite-volume time-domain (FVTD) methods, which are suitable for the meshless method, have been compared. The bistatic RCS of a 2-D cylinder irradiated by transverse magnetic wave (TM wave) or transverse electric wave (TE wave) and a 3-D sphere irradiated by different polarization waves are calculated by the meshless method based on different boundary conditions. The numerical results show that the bistatic RCS calculated by the first boundary condition is closest to the series solution, which indicates that the scattering electric field on the surface of perfect conductors is only related to the incident electric field, and the scattering magnetic field is related to the scattering magnetic field near the body surface and the variation of the normal scattering electric field on the body surface. Finally, based on the selected optimal body surface boundary condition, the paper present the electromagnetic scattering field and the bistatic RCS for a 3-D stealth aircraft model, which shows the ability of the meshless method in dealing with 3-D practical problems to a certain extent.